2017
DOI: 10.4172/2329-9096.1000411
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparetic Stroke Rehabilitation Using Avatar and Electrical Stimulation Based on Non-invasive Brain Computer Interface

Abstract: Brain computer interfaces (BCIs) have been employed in rehabilitation training for post-stroke patients. Patients in the chronic stage, and/or with severe paresis, are particularly challenging for conventional rehabilitation. We present results from two such patients who participated in BCI training with first-person avatar feedback. Five assessments were conducted to assess any behavioural changes after the intervention, including the upper extremity Fugl-Meyer assessment (UE-FMA) and 9 hole-peg test (9HPT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Based on the assessment, 7 studies were determined to be of "good quality", while 4 studies were evaluated as "fair quality" (Supplementary Table S1). In addition, five case reports (23,37,38,40,42) were included and appraised using the "Joanna Briggs Institute (JBI) Critical Appraisal" tool. The overall quality of each case report was "good" based on the JBI checklist (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the assessment, 7 studies were determined to be of "good quality", while 4 studies were evaluated as "fair quality" (Supplementary Table S1). In addition, five case reports (23,37,38,40,42) were included and appraised using the "Joanna Briggs Institute (JBI) Critical Appraisal" tool. The overall quality of each case report was "good" based on the JBI checklist (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Reported RCTs (17, 32-36, 51, 55, 56) and feasibility studies (19,21,23,24,38,42,44,58) claimed statistical significance results; however, their sample size is not large enough (lies between 1 and 51 stroke patients in one group). According to Kaptein (94), a conventional RCT requires a group size of at least 64 individuals in each group to obtain statistically significant results.…”
Section: Small Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a VR avatar shows the same movement on a computer screen in front of the patient. Preliminary data of a clinical study shows a Fugl-Meyer Score improvement of 8 points in sub-acute and chronic patients (N = 25, p < 0.0001) and patients achieve a high BCI classification accuracy [121,122]. José Millán presented a clinical study showing that BCI coupled to FES elicits significant, clinically relevant, and lasting motor recovery of arm and hand function in chronic stroke survivors, while this was not the case for sham FES where stimulation was random and not contingent on cortical patterns of motor activity indicating attempted movement [123].…”
Section: Bcis For Stroke Rehabilitationmentioning
confidence: 98%
“…All patients achieved high control accuracies and exhibited improvements in motor function. In a later study, Cho et al [23] present the results of two patients who performed the BCI training with first-person avatar feedback. After the study, both patients reported improvements in motor functions and both have improved their scores on Upper Extremity Fugl-Meyer Assessment scale.…”
Section: Introductionmentioning
confidence: 99%